2020
DOI: 10.1111/jocd.13866
|View full text |Cite
|
Sign up to set email alerts
|

Study on the skin status of mid‐pregnancy women based on lipidomics

Abstract: Background: Pregnancy is a complex physiological state and its unique changes in skin state have been discussed. Skin surface lipid (SSL) is an important molecular basis for this skin condition, and it affects skin condition in a number of ways, but there are no complete research data on it. Objectives: To analyze the lipidome profiles of SSL in pregnancies and controls in order to understand SSL changes in pregnancy. It will provide theoretical data of SSL on skin care and prevention of skin diseases during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A sample can be collected easily and non-invasively via a gentle swab of skin areas rich in sebum (for example the face, neck or back). Characteristic features have previously been identified from sebum for a limited number of conditions such as Parkinson's Disease and Type 1 Diabetes Mellitus; [ 10 , 11 , 12 ] sebum changes have also been reported in pregnancy [13] . In addition, whilst the mechanisms for the role of sebum in barrier function are not fully described, sebum lipids provide this function directly and also through commensal bacteria interactions; lipid dysregulation would have implications for skin health [14] .…”
Section: Introductionmentioning
confidence: 99%
“…A sample can be collected easily and non-invasively via a gentle swab of skin areas rich in sebum (for example the face, neck or back). Characteristic features have previously been identified from sebum for a limited number of conditions such as Parkinson's Disease and Type 1 Diabetes Mellitus; [ 10 , 11 , 12 ] sebum changes have also been reported in pregnancy [13] . In addition, whilst the mechanisms for the role of sebum in barrier function are not fully described, sebum lipids provide this function directly and also through commensal bacteria interactions; lipid dysregulation would have implications for skin health [14] .…”
Section: Introductionmentioning
confidence: 99%
“…We studied the SSL of 99 young women (Asians, 53 women in mid‐pregnancy and 46 non‐pregnant women; age 18–35 years) and found that the TLs content of women in the middle pregnancy was significantly lower than non‐pregnant women. The results of screening important different lipids showed that the FAs, TG and diglyceride (DG) contents of women in the middle pregnancy decreased significantly, and the contents of GPs and Cers were significantly increased 16,17 …”
Section: Lipidomics Indicated Potential Consistency In Lipidome Chang...mentioning
confidence: 99%
“…The results of screening important different lipids showed that the FAs, TG and diglyceride (DG) contents of women in the middle pregnancy decreased significantly, and the contents of GPs and Cers were significantly increased. 16,17…”
Section: Changes Of Ssl In the Middle Of Pregnancymentioning
confidence: 99%